Genome-wide analysis of dental caries and periodontitis combining clinical and self-reported data - Shungin, Dmitry; Haworth, Simon; Divaris, Kimon; Agler, Cary S.; Kamatani, Yoichiro; Keun Lee, Myoung; Grinde, Kelsey; Hindy, George; Alaraudanjoki, Viivi; Pesonen, Paula; Teumer, Alexander; Holtfreter, Birte; et al. (Nature communications, 2019)
Dental caries and periodontitis account for a vast burden of morbidity and healthcare spending, yet their genetic basis remains largely uncharacterized. Here, we identify self-reported dental disease proxies which have similar underlying genetic contributions to clinical disease measures and then combine these in a genome-wide association study meta-analysis, identifying 47 novel and conditionally-independent risk loci for dental caries. We show that the heritability of dental caries is enriched for conserved genomic regions and partially overlapping with a range of complex traits including smoking, education, personality traits and metabolic measures. Using cardio-metabolic traits as an example in Mendelian randomization analysis, we estimate causal relationships and provide evidence suggesting that the processes contributing to dental caries may have undesirable downstream effects on health. Dental caries and periodontitis are among the most common medical conditions. Here, the authors report a GWAS for measures of oral health that reveals 47 risk loci for caries, find genetic correlation with 31 other complex traits and use Mendelian randomization analyses to explore potential causal relationships.